2021
DOI: 10.3389/fpls.2021.689220
|View full text |Cite
|
Sign up to set email alerts
|

The European Forest Condition Monitor: Using Remotely Sensed Forest Greenness to Identify Hot Spots of Forest Decline

Abstract: Forest decline, in course of climate change, has become a frequently observed phenomenon. Much of the observed decline has been associated with an increasing frequency of climate change induced hotter droughts while decline induced by flooding, late-frost, and storms also play an important role. As a consequence, tree mortality rates have increased across the globe. Despite numerous studies that have assessed forest decline and predisposing factors for tree mortality, we still lack an in-depth understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 67 publications
(195 reference statements)
0
34
0
Order By: Relevance
“…For a complete picture, it would be useful to combine canopy cover loss records with complementary products. These could either be anomalies of spectral indices related to forest vitality [80] or climatological and other environmental data [2,81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a complete picture, it would be useful to combine canopy cover loss records with complementary products. These could either be anomalies of spectral indices related to forest vitality [80] or climatological and other environmental data [2,81].…”
Section: Discussionmentioning
confidence: 99%
“…While our product shows less canopy cover loss in deciduous forests, it records much larger canopy cover loss in coniferous forests compared to the maps of the global forest watch. Other European or nationwide products in Germany do not explicitly determine canopy cover loss (e.g., [80]) and are therefore difficult to compare with our map. While national forest disturbance mapping systems were recently proposed for other Central European countries (e.g., Austria [19]), a national system does not yet exist for Germany, even though remote sensing is considered an important asset to complement ground surveys and the technology is being established at the federal state level [82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…This study identified specific aspects of the meteorological storyline (the three-year evolution of seasonal temperature, T 2m ′ 90d , and precipitation anomalies, P ′ 90d ), which is characteristic for events of low summer forest greenness at the 50 km scale in Europe in 2000-2020. Forest greenness as measured by the N DV I is used to detect reduced forest performance -an early warning mechanism of forest decline (Buras et al, 2021). In temperate forests, low N DV I events are preluded by extraordinarily persistent warm periods, and an unusual accumulation of dry periods over two years.…”
Section: Caveatsmentioning
confidence: 99%
“…Although some forest ecosystems are adapted to low summer water availability, e.g., in the summer-dry Mediterranean or in dry inner-Alpine regions, extended and more frequent hot droughts will strongly affect their dynamics including growth and survival (Rigling et al, 2013;Tague et al, 2019;Ogaya et al, 2020). In this context, forest greenness is an effective measure related to forest performance to monitor the recent forest decline in Europe (Orth et al, 2016;Buras et al, 2020Buras et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The information obtained in this study provides input to both forest management and landscape planning striving for ecosystem resilience and an ecosystem-based adaptation to climate change. Existing monitoring apps such as the European Forest Condition Monitor (Buras et al, 2021) or the Waldmonitor (Welle et al, 2022) focus on vegetation vitality. Extending this monitoring with analyses of forest fragmentation can contribute to the understanding of forest vulnerability.…”
Section: Introductionmentioning
confidence: 99%